Development prospects of the rotary combustion engine as a car power unit (Academic journal Industrial Machine Building Civil Engineering, 2022)
The article briefly describes the main advantages and disadvantages of a rotary combustion engine as a car power unit and considers the option of improving the engine performance specifications due to the use of hydrogen as a fuel. Analyzing the researches, it was established the possibility of hydrogen rotary combustion engines safe work and improvement of the fuel mixture combustion indicators. Hydrogen rotary engines have been found to have low emissions. A scheme for integrating the hydrogen injection system into the design of a rotary internal engine is proposed. The operation of the apex seal between the rotor and the engine block was studied by modeling. It is reasonable to assume that rotary engines equipped to run on hydrogen fuel in the future can potentially be used as car power units, but today their design still needs further technological improvement.
Keywords: combustion; emission; fuel injection; hydrogen; rotary engine